Soy Protein Isolate Improved the Properties of Fish Oil-Loaded Chitosan–Sodium Tripolyphosphate Capsules - Yunning Wang; Mubeen Asad; Deqian Wang; Xiaofan Gao; Guoliang Zheng; Jian Zhong; Jing Xie; Zhengquan Wang (Foods)
In this paper, the effect of soybean isolate protein (SPI) content on the physicochemical properties and oxidative stability of chitosan–sodium tripolyphosphate (CS-STPP)-loaded fish oil capsules was investigated. The SPI/CS-STTP capsules formed after the addition of different amounts of SPI were larger in size and more homogeneous in morphology than the CS-STPP capsules, and the SPI was encapsulated on the surface of the CS matrix, altering the surface properties and morphology of the particles. The study of different CS-to-SPI blend ratios (1:0, 3:1, 2:1, 1:1, 1:2) showed that the water content of the microcapsules increased from 49.79% to 53.27–64.99%, the fish oil loading increased from 17.06% to 18.31–24.89%, and the encapsulation rate increased from 89.42% to 93.90–96.14%. In addition, the addition of SPI reduced the maximum peroxide value from 445 to 264 meq/kg oil. In the simulated in vitro digestion experiments, the addition of various amounts of SPI resulted in a significantly lower percentage of final free fatty acid (FFA) release than observed for CS-STPP capsules alone. These changes observed in the properties may be due to structural differences between CS-STPP capsules and SPI/CS-STPP capsules. All the results confirm that the obtained capsules are promising for the development of functional foods and drugs.